Effect of indoor air quality of day care centers in children with different predisposition for asthma - Carreiro-Martins, Pedro (2018)
BACKGROUND: Scarce information is available about the relationships between indoor air quality (IAQ) at day care centers (DCC), the estimated predisposition for asthma and the actual wheezing susceptibility. METHODS: In the Phase II of ENVIRH study, 19 DCC were recruited after cluster analysis. Children were evaluated firstly using the ISAAC questionnaire and later by a follow up questionnaire about recent wheezing. A positive asthma predictive index (API) was considered as predisposition for asthma. Every DCC was audited for IAQ and monitored for chemical and biological contaminants. RESULTS: We included 1,191 children, with a median age of 43 (P25 -P75 : 25-58) months. Considering the overall sample, in the first questionnaire, associations were found between CO2 concentration (increments of 200 ppm) and diagnosis of asthma (OR: 1.10; 95% CI: 1.00 - 1.20). Each increment of 100 μg.m-3 of total volatile organic compounds (TVOC) and 1 μg of Der p1/g of dust were associated with wheezing in the previous 12 months (OR: 1.06; 95% CI: 1.01-1.11 and OR: 1.06; 95% CI: 0.99-1.12, respectively). In the follow-up questionnaire, TVOC were again associated with wheezing (OR: 1.05; 95% CI: 1.00-1.11). Children exposed to fungal concentration above the 75th percentile had also higher odds of wheezing at follow-up. TVOC were associated with wheezing in children with either negative or positive API. CONCLUSIONS: IAQ in DCC seems to be associated with wheezing, in children with and without predisposition for asthma. This article is protected by copyright. All rights reserved.